Altered Bioavailability of Nitric Oxide and L-Arginine Is a Key Determinant of Endothelial Dysfunction in Preeclampsia. (22nd October 2020) - Tashie, Worlanyo; Fondjo, Linda Ahenkorah; Owiredu, William K. B. A.; Ephraim, Richard K. D.; Asare, Listowell; Adu-Gyamfi, Enoch Appiah; Seidu, Laila
Abstract : Background . Preeclampsia is a major cause of maternal and neonatal morbidity and mortality in sub-Saharan Africa. Evidence indicates that endothelial dysfunction is central to the pathogenesis of preeclampsia. This study assessed the level of the components of the arginine-nitric oxide pathway to evaluate endothelial dysfunction in normotensive pregnancies and pregnancies complicated with preeclampsia. Methods . This case-control study was conducted among pregnant women who visited Comboni Hospital from January 2017 to May 2018. A total of 180 pregnant women comprising 88 preeclamptic women (PE) and 92 healthy normotensive pregnant women (NP) were recruited. Sociodemographic, clinical, and obstetric data were obtained using validated questionnaires. Blood pressure and anthropometrics were measured, and blood samples were collected for the estimation of nitric oxide (NO ∙ ), L-arginine, asymmetric dimethylarginine (ADMA), and 3-nitrotyrosine using an enzyme-linked immunosorbent assay technique. Results . The mean NO ∙ (p = 0.010 ) and L-arginine/ADMA ratio (p < 0.0001 ) was significantly lower in PE compared to NP while mean L-arginine (p = 0.034 ), ADMA (p < 0.0001 ), and 3-nitrotyrosine (p < 0.0001 ) were significantly higher in PE than NP. ADMA showed a significant positive association with systolic blood pressure (β = 0.454, p = 0.036 ) in severe PE. Women with PE had significant intrauterine growth restriction (p < 0.0001 ) and low birth weight infants (p < 0.0001 ) when compared to NP. Conclusion . Preeclampsia is associated with reduced NO ∙ bioavailability, L-arginine/ADMA ratio, and elevated levels of ADMA and 3-nitrotyrosine. Measurements of the levels of these parameters can help in the early prediction of endothelial dysfunction in preeclampsia. Exogenous therapeutic supplementation with L-arginine during pregnancy to increase the L-arginine/ADMA ratio should be considered to improve endothelial function in preeclampsia and pregnant women at risk of developing preeclampsia.